The Effect of Reward, Punishment on Satisfaction and Work Ethic and its Implication on Organizational Commitment (Empirical Study on Ministry of Religious Affairs Employees in the South Papua Province Region) - Lestari, Aloysia Maria Sri Hastuti; Erari, Anita; Handoyo, Sarwo Edy (East Asian Journal of Multidisciplinary Research, 2024)
The research focused on the effect of the reward and punishment system on the level of satisfaction and work ethic of employees, and how to influence the organizational commitment of employees at the Office of the Ministry of Religion in the South Papua Province Region. The type of research used is quantitative. The total population totaled 159 people. The sampling technique uses a saturated sampling approach (census), which involves all members of the population. Data collection procedures through online questionnaires. The results of this study indicate that reward has a significant positive effect on job satisfaction, reward has a significant positive effect on work ethic, reward has no significant effect on organizational commitment, punishment has no significant effect on job satisfaction, punishment has no significant effect on work ethic, punishment has no significant effect on organizational commitment, job satisfaction has a significant positive effect on organizational commitment, work ethic has a significant positive effect on organizational commitment, job satisfaction mediates the effect of reward on organizational commitment, work ethic mediates the effect of reward on organizational commitment, job satisfaction does not mediate the effect of punishment on organizational commitment, work ethic does not mediate the effect of punishment on organizational commitment.